Direct Radial LMHF Microvibration Induced Bone Formation and Promoted Implant Osseointegration. (22nd May 2014) - Wang, Shirui; Liu, Yang; Tang, Yi; Zhao, Wei; Li, Junying; Yang, Yang; Du, Wen; Yu, Haiyang
Abstract: Background: Mechanical loading is known to play an important role in bone remodeling. Purpose: This study aimed to evaluate the effect of direct low‐magnitude high‐frequency (LMHF) microvibration on dental implant bone formation and osseointegration. Materials and Methods: Titanium implants were installed in rabbit tibiae. The implants in the left legs were loaded with mechanical vibration (15 μm) at 10, 20, 30, and 40 Hz (10, 20, 30, and 40 Hz groups, respectively) for 30 minutes every day. The implants on the right legs were used as a sham control and did not receive a vibration load. Results: After 20 days, the 10, 20, and 30 Hz groups showed significantly greater newly formed bone volume, density, ratio of the bone surface area to the trabecular bone surface area, and ratio of the bone surface area in direct contact with osteoclasts versus the total bone surface area in the region of interest compared with the sham control group, especially the 20 Hz group. However, the 40 Hz group did not. Conclusions: In conclusion, the application of direct LMHF (10, 20, or 30 Hz) vibration on the implants promoted bone formation and osseointegration, especially at 20 Hz; however, the use of 40 Hz did not result in any significant improvement.